MOTIF DUKUNGAN RELAWAN INDEPENDEN TERHADAP ELEKTABILITAS PRABOWO-SANDI PADA PILPRES 2019: STUDI ATAS GERAKAN MILENIAL INDONESIA (GMI) YOGYAKARTA - Kurnia, Rahmat Kahfi; Al-Hamdi, Ridho (JPP (Jurnal Politik Profetik), 2019)
This paper examines the motives of the independent volunter’s support toward the electability of Prabowo-Sandi in the 2019 presidential election. There three motives which will be used as the indicators: incentive-material motive, incentive-solidarity motive, and incentive-idealism motive. The Indonesian Millennial Movement (GMI) is being the selected case of the research because this organization is one of the active independent movements among millennials which campaigns for the  electability of Prabowo-Sandi to the public in Yogyakarta Special Region. It is a qualitative research by applying the case study approach to find out the motives of GMI’s support in winning Prabowo-Sandi in the 2019 presidential election. Documentary and in-depth interview were utilized as the data-gathering. The finding demonstrates that GMI combines all three motives in supporting the candidate. Thus, GMI had a mix incentive motive as its strategy to support Prabowo-Sandi. Nonetheless, incentive-solidarity motive was the most frequently applied by GMI among other motives.